Evaluation of the Quality of Life in newly Recognized Cancer Patients - Tabari F; Zakeri Moghadam M; Bahrani N; Monjamed Z (Tehran University of Medical Sciences, 2007)
Background & Objective: The chronic diseases such as cancer could seriously affect health and consequently quality of life of individuals. The purpose of this study is to evaluate the quality of life in the patients who have been recently diagnosed with caner."nMethods & Materials: This research is a descriptive - analytical study aims to determine quality of life in newly diagnosed cancer patients in selected oncology clinics of Tehran University of Medical Sciences. In this research, 196 newly diagnosed cancer patients were selected by simple sampling method and based on aim. The data were collected by a questionnaire including demographic data, disease characteristic and questions about quality of life in physical, physiological and socioeconomic aspects. The socioeconomic questionnaire presented to the patients after his/ her permission and giving necessary descriptions to him/ her about the objectives of the research. The questions were read for illiterate patients by researcher. The SPSS program was used for data analysis. Descriptive statistics such as absolute/ relative and average sufficiency and deductive statistics such as 2 test were used as well."nResults: The research results show that the quality of life in physical aspect is desirable in majority (67/9%) of patients. The quality of life in physiological aspect is desirable in majority (63.3%) of patients and as well the quality of life in socioeconomic aspect is desirable in majority (76.5%) of patients. The research conclusion shows that there is a meaningful relationship between number of children and economic status (P<0.001) and quality of life in physical aspect. There is a meaningful relationship between economic status with quality of life in psychological aspect and with quality of life in socioeconomic aspect (P<0.05). There is a meaningful relationship between type of cancer, disease stage at the time of diagnosis (P<0.001), and quality of life in physical aspect. There is a meaningful relationship between disease stage (P=0.002), and quality of life in psychological aspect and quality of life in socioeconomic aspect (P<0.05)."nConclusion: The research result shows that the quality of life in physical, psychological and socioeconomic aspects is desirable in the society. Thus the nurses can play an important role in increasing the quality of life of such patients.